Developing social entrepreneurial capability in Thai community enterprises: The roles of intellectual capital, creating shared value, and organizational agility on sustainability - Phiphop Somwethee; Jintanee Ru-Zhue; Somnuk Aujirapongpan; Anuman Chanthawong; Berto Usman (Social Sciences and Humanities Open)
The aim of this article is to examine the relationships and influences of intellectual capital, creating shared value, and organizational agility on social entrepreneurial capacity and sustainable organizational performance. It also aims to provide guidelines for enhancing social entrepreneurial capabilities and fostering sustainability from these perspectives. A survey was conducted using a questionnaire with 400 community enterprises registered with the Department of Agricultural Extension in Phuket, Phang Nga, and Krabi provinces, targeting business executives. Data analysis included averages, skewness, kurtosis, and standard deviation, with structural equation modeling (SEM) performed using the AMOS program. The results highlight significant relationships between intellectual capital, creating shared value, and organizational agility in driving social entrepreneurial capabilities and long-term organizational success. Intellectual capital positively influences creating shared value, organizational agility, and social entrepreneurial capabilities. creating shared value further strengthens organizational agility and social entrepreneurial potential. Organizational agility, in turn, enhances social entrepreneurial capabilities and long-term performance. Additionally, social entrepreneurial capability positively impacts long-term organizational success. The policy recommendations emphasize fostering intellectual capital, promoting creating shared value, balancing agility, supporting social entrepreneurialism, integrating shared value into strategy, monitoring overall performance, encouraging continuous learning, and fostering collaboration within and across industries. The development of social entrepreneurial capabilities in communities depends on leveraging intellectual capital to drive creating shared value and organizational cohesion, ultimately supporting long-term sustainability.